The impact of supply chain integration on the operational process performance: An empirical study under the perspective of Resource Orchestration Theory - Rinaldo de Castro Oliveira; Inayara Valéria Defreitas Pedroso Gonzalez (BBR: Brazilian Business Review)
The research evaluated the dimensions that compose the supply chain integration - SCI and their impact on the performance of companies’ operational processes. SCI was evaluated based on the Resource Orchestration Theory, and the performance was measured in the level of business processes of the Supply Chain Operation Reference (SCOR) model. A quantitative approach was used, and a questionnaire was applied in Brazilian companies of different sectors. The data were analyzed using structural equation modeling, and the results confirmed the premise that SCI is a multidimensional construct composed by the constructs synchronized planning, strategic partnership, operational coordination and information integration, that have a complementary and interdependent relation. Moreover, SCI has a significant and considerable impact on the operational performance, supporting the assumption that this effect should be examined in the level of business processes, where first-order results are frequently observed.